STUDY OF ORGANOLEPTIC AND PHYSICAL AND CHEMICAL CHARACTERISTICS OF PRODUCTS FROM SMOKING ROLLING TOBACCO - E. Y. Smirnova; E. V. Gnuchikh; D. D. Kirillov; A. A. Slavyansky (Новые технологии, 2022)
Products from rolling smoking tobacco, they are also “hand-rolled”, are currently a trending phenomenon in the development of the tobacco products market, both in the Russian Federation and abroad. In view of the fact that maximum allowable values for the content of nicotine, tar and carbon monoxide in smoke are set for cigarettes, manufacturers produce tobacco blendings for cigarettes with a high content of components such as reconstituted tobacco and extended stem, on the one hand, regulating toxicity, and on the other hand, reducing flavoring properties. This leads to the fact that modern cigarettes, in terms of taste and aroma of tobacco smoke, poorly meet consumer taste preferences. By creating products from rolling smoking tobacco, combining different types of tobacco, using paper for self-rolling paper of different composition and breathability, as well as changing the mass of tobacco and the diameter of the product, the consumer can create an ideal product that meets all his taste preferences. In connection with the growing popularity of hand-rolled cigarettes, the relevance of research on their qualitative characteristics is growing. This article discusses such qualitative characteristics as the chemical composition and technological properties of samples: raw tobacco; tobacco blendings with and without a vein; rolling smoking tobacco of various brands. The main purpose of the research is to study the influence of the design of the product (diameter, weight, air permeability of paper) on the tasting assessment. For each type of smoking tobacco, products (hand-rolled) of various weights and diameters have been made, using four types of paper, differing in composition and air permeability. The dependence of the tasting evaluation of products from rolling smoking tobacco on the air permeability of the paper and the design features of the products (fiber width, weight and diameter of the products) has been established.